Mycota of understudied biodiversity hotspots, deep DNA sequencing reveals hyperdiverse communities and strong habitat partitioning along altitudinal gradients in cloud forest communities in Borneo and in the Andes - Geml, József (2014)
Cloud forests are not only among the world´s most biologically important ecosystems with their tremendous biodiversity and high rateof endemism, but they also provide crucial water supplies to human settlements and agricultural areas. Mount Kinabalu in Borneo and the Yungas forest on the eastern slopes of the Andes have been known tobe particularly rich in plant and animal species and both have been designated as UNESCO Biosphere Reserves. Based on proportional diversity estimates around the globe, the fungi are at least asdiverse (probably even more). Yet, virtually nothing is known aboutthe true diversity and distribution patterns of fungi in theseregions. We carried out Ion Torrent sequencing of soil samples takenalong multiple altitudinal gradients in the Yungas in Argentina andon Mount Kinabalu and in the Crocker Range in Malaysian Borneo. Thesamples represent all major altitudinal forest types from ca. 500 to2500 m in the Yungas and from 300 to 4000 m in Borneo. Our resultssuggests that the sampled communities are very diverse, harbouringnumerous undescribed and/or previously unsequenced taxa. NMDSanalyses suggested that fungal community composition correlatedstrongly with forest type, with many OTUs showing strong preferencefor a certain elevation zone. Several ecological groups showedsimilar distributional trends in the two regions, e.g., saprobicfungi were more diverse at lower elevations, while root endophyteswere more dominant at higher altitudes. Our data offer anunprecedented insight into the diversity and spatial distribution offungi in tropical and subtropical cloud forests.